Travellin' mama : mothers, mothering and travel - Beyer, Charlotte, 1965-; MacLennan, Janet; Silva, Dorsía Smith; Tesser, Marjorie (Demeter Press, 2019)
""Don't women with children travel?"" Marybeth Bond and Pamela Michael enquire, in their book A Mother's World: Journeys of the Heart (1998), when discovering the absence of portrayals of travelling mothers. Addressing this absence, our book Travellin' Mama: Mothers, Mothering and Travel explores the multiple dimensions of motherhood and travel. Through a variety of compelling creative pieces and critical essays with a global outlook and wide-ranging historical, cultural, and national perspectives, Travellin' Mama: Mothers, Mothering and Travel examines the vital contributions made to travel w